2019
DOI: 10.1002/term.2818
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for controlling egress of therapeutic cells from hydrogel microcapsules

Abstract: Endothelial progenitor cells and human mesenchymal stem cells (hMSCs) haveshown great regenerative potential to repair damaged tissue; however, their injection in vivo results in low retention and poor cell survival. Early clinical research has focussed on cell encapsulation to improve viability and integration of delivered cells. However, this strategy has been limited by the inability to reproduce large volumes of standardized microcapsules and the lack of information on cell-specific egress and timed releas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
3
11
0
Order By: Relevance
“…Nanoporous hydrogels have been previously used to encapsulate single cells forming a “microgel” niche to protect cells for in vivo delivery 23 . A microfluidic approach 27,28 was employed to encapsulate EVs labelled with pkh26 in 1% agarose-1% gelatin producing microgels of uniform size (47 ± 0.4 μm) ( Figure 2A-C ). Labelled EVs were detected within microgels evenly dispersed throughout the spherical microgel as observed using confocal imaging z-stacks ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nanoporous hydrogels have been previously used to encapsulate single cells forming a “microgel” niche to protect cells for in vivo delivery 23 . A microfluidic approach 27,28 was employed to encapsulate EVs labelled with pkh26 in 1% agarose-1% gelatin producing microgels of uniform size (47 ± 0.4 μm) ( Figure 2A-C ). Labelled EVs were detected within microgels evenly dispersed throughout the spherical microgel as observed using confocal imaging z-stacks ( Figure 2D ).…”
Section: Resultsmentioning
confidence: 99%
“…Extracellular vesicles were encapsulated using a novel microfluidic device designed for cell and small particle encapsulation, in a similar manner as described for cell encapsulation 27,28 . In brief, a known quantity of EV protein was mixed with 1% ultra-low gelling temperature agarose (Sigma Aldrich, Oakville, ON, Canada), 1% gelatin (Sigma Aldrich, Oakville, ON, Canada) and kept at 37°C during encapsulation.…”
Section: Methodsmentioning
confidence: 99%
“…Similarly, combinations of natural and synthetic polymers can be combined with temperature responsive moieties to obtain hydrogels with unique swelling and gelling properties (Jiang et al, 2019a). Such composite hydrogels can also allow for finetuning of hydrogel degradation (Benavente Babace et al, 2019;Neubauer et al, 2019), which offers lots of potential for in vivo applications. In addition, alterations can facilitate complex techniques that would be extremely difficult or impossible with natural hydrogels.…”
Section: Synthetic Hydrogelsmentioning
confidence: 99%
“…When hydrogel microspheres are used as cell carriers, it is found that the cells distributed along the border of the hydrogel droplets tend to escape upon droplet crosslinking and during subsequent culturing. [114,115] Thus, the laden cells are expected to be focused on the center of the droplets to reduce or avoid cellular escape. In one study, microfluidic platform was placed on an orbital shaker that orbited at 1000 rpm during droplet crosslinking to achieve robust positioning of individual MSCs in the center of hydrogel microspheres.…”
Section:  Distribution Control Of Cargosmentioning
confidence: 99%